Spread through air spaces (STAS): prognostic impact of a semi-quantitative assessment - Warth, Arne (Journal of thoracic disease, 2017)
Following validation in two large independent cohorts from the US and Germany (1,2), the concept of spread through air spaces (STAS) was introduced for pulmonary adenocarcinomas (ADC) in the 2015 World Health Organization (WHO) Classification for lung cancer and subsequently validated and extended (3). Now, Uruga et al . provided evidence that a semi-quantitative assessment of STAS might provide additional prognostic information (4).